Besnoitia besnoiti tachyzoite replication in bovine primary endothelial cells relies on host Niemann–Pick type C protein 1 for cholesterol acquisition - Larrazabal, Camilo; Hermosilla, Carlos; Taubert, Anja; Silva, Liliana M. R. (Frontiers in Veterinary Science, 2024)
Besnoitia besnoiti is a cyst-forming apicomplexan parasite and the causal agent of bovine besnoitiosis. During early phase of infection, tachyzoites replicate within host endothelial cells in a host cell cholesterol-dependent process. By applying U18666A treatments, we here evaluated the role of Niemann-Pick type C protein 1 (NPC1) in both, intracellular B. besnoiti replication and host cellular cholesterol distribution. Additionally, B. besnoiti-driven changes in NPC1 gene transcription were studied by qPCR. Overall, U18666A treatments significantly reduced B. besnoiti proliferation and induced cholesterol accumulation in host cytoplasmic dense vesicles. However, NPC1 gene transcription was not affected by B. besnoiti infection.